Pengaruh Pemberian Kombinasi Jus Buah Naga (Hylocereus polyrhizus) dan Air Rebusan Daun Kersen (Muntingia calabura) pada Penderita DM (Tipe 2): Effect of Combination of Dragon Fruit (Hylocereus polyrhizus) Juice and Kersen Leaf (Muntingia calabura) Boiled Water in DM (Type 2) Patients - Aprilia Putri Firdaus; Mukti Priastomo; Hadi Kuncoro (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Diabetes mellitus is a disease characterized by an increase in blood glucose levels, which prevalence in East Kalimantan in 2018 is the third highest in Indonesia. Kersen leaves and dragon fruit are believed to regulate blood glucose levels in people with type 2 diabetes mellitus and can be used as a complementary therapy. This study aims to see the characteristics, determine the organoleptic assessment of the combination of dragon fruit juice with kersen leaves boiled water and its effect on blood glucose levels, blood pressure, heart rate, body weight, and the frequency of polyuria, polyphagia, and polydipsia in patients type 2 diabetes mellitus at Klinik Semoga Sehat Samarinda. The research method used was quasi experimental with pre-test and post-test procedures. The data obtained from the characteristics were 70% aged 50-59 years, 70% women, 50% diploma/bachelor, 60% housewives. For organoleptic assessment, it was found that 70% liked the taste, texture, aroma and color and 50% did not feel bitter. The combination of dragon fruit with kersen leaves boiled water had an effect on reducing blood glucose levels significantly (P 0.05) and there was a change in the frequency of polyuria, polyphagia, polydipsia by 80% did not urinate frequently and were not often thirsty and 90% were less hungry.